Transformation of the real estate and construction industry: empirical findings from Germany - Andreas Pfnür; Benjamin Wagner (Journal of Business Economics, 2020)
The German real estate and construction industry is facing a transformation, triggered by fundamental changes in technology, the economy and society. The purpose of this paper is to explore how these changes exert pressure to adapt on existing business models, while also offering opportunities for their further development. A model that attributes the transformation of the real estate industry to megatrends, specific structural change drivers, business models and the interaction of the groups of players in the value creation system is developed. The model is tested empirically by a survey. Structural equation modelling is used to measure the impact of various determinants of transformation and the relevance of adaptation strategies to the different groups of players. As a result, the study explains three impact mechanisms of the transformation in the real estate industry. The transformation originates from the occupiers, who need more flexible space and are focusing on holistic solutions that are not provided by the real estate industry. Service providers are striving to increase the efficiency of their traditional processes, rather than evolving new business models or services. The investors recognise the increasing importance of the occupiers but they are rarely pursuing the resulting strategies. Property developers recognise these requirements: their adaptation strategies most strongly question their previous business. For practitioners, the results point out the opportunities and risks of transformation and help to illustrate the need for change. For academicians, the results indicate a way to explain and measure the transformation of a value creation system.
Keywords: R30; O33; Z10; 650; Real estate management; Real estate transformation; Structural change; Strategic management; Real estate trends